A Synthetic Lethal Screen Identifies a Role for Lin-44/Wnt in C. elegans Embryogenesis - Hartin, Samantha N. (PLoS One, 2015)
BACKGROUND: The C. elegans proteins PTP-3/LAR-RPTP and SDN-1/Syndecan are conserved cell adhesion molecules. Loss-of-function (LOF) mutations in either ptp-3 or sdn-1 result in low penetrance embryonic developmental defects. Work from other systems has shown that syndecans can function as ligands for LAR receptors in vivo. We used double mutant analysis to test whether ptp-3 and sdn-1 function in a linear genetic pathway during C. elegans embryogenesis. RESULTS: We found animals with LOF in both sdn-1 and ptp-3 exhibited a highly penetrant synthetic lethality (SynLet), with only a small percentage of animals surviving to adulthood. Analysis of the survivors demonstrated that these animals had a synergistic increase in the penetrance of embryonic developmental defects. Together, these data strongly suggested PTP-3 and SDN-1 function in parallel during embryogenesis. We subsequently used RNAi to knockdown ~3,600 genes predicted to encode secreted and/or transmembrane molecules to identify genes that interacted with ptp-3 or sdn-1. We found that the Wnt ligand, lin-44, was SynLet with sdn-1, but not ptp-3. We used 4-dimensional time-lapse analysis to characterize the interaction between lin-44 and sdn-1. We found evidence that loss of lin-44 caused defects in the polarization and migration of endodermal precursors during gastrulation, a previously undescribed role for lin-44 that is strongly enhanced by the loss of sdn-1. CONCLUSIONS: PTP-3 and SDN-1 function in compensatory pathways during C. elegans embryonic and larval development, as simultaneous loss of both genes has dire consequences for organismal survival. The Wnt ligand lin-44 contributes to the early stages of gastrulation in parallel to sdn-1, but in a genetic pathway with ptp-3. Overall, the SynLet phenotype provides a robust platform to identify ptp-3 and sdn-1 interacting genes, as well as other genes that function in development, yet might be missed in traditional forward genetic screens.